The underlying mechanisms of arenaviral entry through matriglycan - Katz, Michael; Diskin, Ron (Frontiers in Molecular Biosciences, 2024)
Matriglycan, a recently characterized linear polysaccharide, is composed of alternating xylose and glucuronic acid subunits bound to the ubiquitously expressed protein α-dystroglycan (α-DG).Pathogenic arenaviruses, like the Lassa virus (LASV), hijack this long linear polysaccharide to gain cellular entry. Until recently, it was unclear through what mechanisms LASV engages its matriglycan receptor to initiate infection. Additionally, how matriglycan is synthesized onto α-DG by the Golgiresident glycosyltransferase LARGE1 remained enigmatic. Recent structural data for LARGE1 and for the LASV spike complex informs us about the synthesis of matriglycan as well as its usage as an entry receptor by arenaviruses. In this review, we discuss structural insights into the system of matriglycan generation and eventual recognition by pathogenic viruses. We also highlight the unique usage of matriglycan as a high-affinity host receptor compared with other polysaccharides that decorate cells.